Situation of the inclusion of women and young people in agricultural and rural areas in Côte d'Ivoire: Study Report - Yeo, P.; Arouna, A.; Mobio, A.; Kra, G.; Mujawamariya, G. (AfricaRice, 2024)
From 7 to 17 February 2024, data was collected on the situation regarding the inclusion of women and young people in agricultural and rural areas in Côte d'Ivoire. It is part of one of the TAFS-WCA's priority objectives, which is to examine in greater depth the obstacles to the empowerment of vulnerable groups in agricultural value chains. The research approach is qualitative and ethnographic. The surveys covered two distinct cultural areas, namely the village of Angôkou-Appiakro (Bouake department) and Dikouéhi Palegnoa (Gagnoa department). Stakeholder consultations were based on Focus Group Discussions (FGD) and semi-structured interviews. A total of 58 agricultural stakeholders were interviewed in the selected communities. The data was analysed using an approach that prioritised their opinions. In the village of Angôkou-Appiakro, the data shows that it is difficult for women to be autonomous. Apart from widows, they have no control over production assets and resources. Men deny them the full freedom and resources they need to do so. As a result, women are excluded from participating in decision-making at community level. They remain under the authority of men. Young people are also particularly vulnerable to economic inequalities because of the mismatch between their aspirations and the social norms in force in their community. They are traditionally sidelined by their social elders in the management of day to-day affairs and resources, which reinforces their precariousness.